The association between fibroblast growth factor 21 with diabetes retinopathy among type 2 diabetes mellitus patients: a systematic review, meta-analysis, and meta-regression - Basir, Herni; Nugrahani, Annisa Salsabilla Dwi; Aman, Andi Makbul; Bakri, Syakib; Rasyid, Haerani; Umar, Husaini; H. P., Faridin; Ichsan, Andi Muhammad; Zainuddin, Andi Alfian (PeerJ, 2024)
Background Diabetic retinopathy (DR), a leading cause of vision loss worldwide, is a common complication of type 2 diabetes mellitus (T2DM) driven by chronic hyperglycemia and microvascular damage. Fibroblast growth factor 21 (FGF21) is crucial in blood sugar regulation and has been linked to DR incidence and severity. While some studies suggest that FGF21 levels may contribute to the DR incidence, others propose a protective role. This discrepancy necessitates further analysis, prompting this study to evaluate the association between FGF21 levels and DR incidence and severity in T2DM patients. Methods A systematic search was conducted through MEDLINE, Web of Science, Scopus, and Embase up to May 2024 for studies evaluating the association between FGF21 and DR incidence and severity. A random-effect model meta-analysis was performed to calculate the pooled standardized mean difference (SMD) and 95% confidence intervals (CI). A univariate meta-regression was performed to analyze factors influencing pooled size estimates. All statistical analyses were performed using STATA 17 software. Result This systematic review and meta-analysis of 5,852 participants revealed that FGF21 was positively correlated with DR (SMD 3.11; 95% CI [0.92–5.30], p = 0.005) and sight-threatening DR (STDR) incidence (SMD 3.61; 95% CI [0.82–6.41], p = 0.01). There was no significant difference in FGF21 levels in DR vs STDR (p = 0.79). Subgroup analysis revealed a significant difference in DR incidence between LDL groups, with higher DR incidence in the group with low-density lipoprotein (LDL) levels >100 (P < 0.00001). Meta-regression revealed no variables significantly influenced the pooled size estimates. Conclusion A higher level of FGF21 was associated with higher DR and STDR incidence among T2DM patients, highlighting its potential utilization as a biomarker for DR detection and enabling the exploration of FGF21-based treatment strategies. However, variables independently predicting DR among patients with elevated FGF21 levels shall be explored further. PROSPERO ID CRD42024559142.
Keywords: Diabetic retinopathy; Fibroblast growth factor; Type 2 diabetes mellitus; Meta-analysis; Meta-regression